Detection of Saint Louis encephalitis virus in two Brazilian states - Moraes, Marília M. [UNESP]; Kubiszeski, Janaina Rigotti; Vieira, Carla J. da Silva Pessoa; Gusmao, Arianne Fagotti [UNESP]; Pratis, Taina Silva [UNESP]; Colombo, Tatiana E.; Thies, Sirlei Franck; do Carmo Araujo, Fabiana; Zanelli, Cleslei F. [UNESP]; Milhim, Bruno Henrique Gonçalves de Aguiar; da Silva, Gislaine C. D.; Nogueira, Maurício L.; et al. (My University, 2022)
We describe the circulation of Saint Louis encephalitis virus (SLEV) in two Brazilian States during outbreaks of Dengue and Zika viruses. We detected the virus in a patient from Araraquara, State of São Paulo, and in patients and in a mosquito pool of Culex quinquefasciatus from Sinop, State of Mato Grosso. Phylogenetic analysis grouped samples from this study within genotype V, which are closely related to other strains that previously circulated in other parts of the country. Genotype V seems to have established circulation in Brazil.
Keywords: arbovirus; Brazil; dengue; phylogenetic analysis; Saint Louis encephalitis virus; viral surveillance